ChemInform Abstract: Synthesis of Cyclic 2‐Oxazolidenes by Chemical CO2 Fixation. Issue 24 (27th May 2016) - Niemi, Teemu; Perea‐Buceta, Jesus E.; Fernandez, Israel; Repo, Timo
Abstract: Review: 22 refs.